Simplify,a) 7 ⋅ | 1 − 4 | 2 ÷ 3b) 3 ( 3 2...

Arectemieryf0

Arectemieryf0

Answered

2022-07-28

Simplify,
a) 7 | 1 4 | 2 ÷ 3
b) 3 ( 3 2 ) 5 ( a 2 ) 8 ( 6 9 ) ÷ ( 3 )
For (b), do top, thus bottom then put together.

Answer & Explanation

Kaiden Weeks

Kaiden Weeks

Expert

2022-07-29Added 14 answers

Step 1
a) 7 | 1 4 | 2 ÷ 3 = 7 | 3 | 2 ÷ 3
= 7 ( 9 ) ÷ 3
= 63 ÷ 3
= 21
Step 2
b) 3 ( 3 2 ) 5 ( 9 2 ) 8 ( 6 9 ) ÷ ( 3 ) = 3 ( 9 ) 5 ( 7 ) 8 ( 3 ) ÷ ( 3 )
= 27 35 24 ÷ ( 3 )
= 8 ( 24 3 )
= 8 8
= 1

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?